Status inconsistency of women: a study in Hamadan, Iran - Babaei, Hamidreza; Zomorrodian, Amir Hossein; Gill, Sarjit S.; Falahati, Leila (Marsland Press, 2011)
This research investigates the status inconsistency among women in Hamadan province, Iran. The study was carried out in eight cities and 32 villages. Questionnaire was applied to collect data from 767 women from urban areas and 786 women from rural area. Data analysis was done by using SPSS software and multi-variable regressions. The results show considerable status inconsistency among women in Hamadan. In addition, with decreasing social status of women here, the status inconsistency increases and the rate of status inconsistency in the rural area was higher than the urban area.